Diagnóstico e genotipagem do helicobacter pylori em amostras de biópsia gástrica, saliva e placa dental - Rasmussen, Lucas Trevizani (2009)
Purpose: The Helicobacter pylori, a gram negative bacterium to colonize human gastric mucosa and has been shown to be strongly associated with chronic gastritis, gastric and duodenal ulcerations and a risk factor for gastric carcinoma. Several studies suggest progressive gastric mucosa damage induced by the patogen. Extensive search for Helicobacter pylori virulence factors lead to the characterizations of a vacuolating cytotoxin A (vacA) and an associated cytotoxin A (cagA). The oral cavity has been implicated as a potential H. pylori reservoir, and may therefore be involved in the reinfection of the stomach, which sometimes follows treatment of H. pylori infection. The objectives of this study were (1) to determine the presence of H. pylori in the oral cavity and (2) to investigate the relationship between oral H. pylori and subsequent gastritis. Methods: Gastric biopsies, saliva and dental plaques were obtained from dyspeptic adults. DNA was extracted and evaluated for the H. pylori and cagA presence, vacA alleles, using polymerase chain reaction and Southern blotting methods. Results: Persons with gastritis had a high frequency of Helicobacter pylori positives in the stomach and there was a statistically significant correlation between gastric biopsies and oral cavity. Conclusions: We shown a high prevalence of the H. pylori and presence with cagA gene associated of vacA s1 alelles in gastric biopsies. Our results suggest a relation between gastric infection and the bacterium in the oral cavity, with a variation of cytotoxin genotype between saliva and dental plaque suggesting a reservoir of the species and that more than one H. pylori strains may exist in the saliva, dental plaque and stomach of the same patient